Role of Structured Career Counselling in Speciality Selection among Post Graduate Trainees - Mahwash Mansoor (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To highlight the relevance, importance and necessity of structured career counselling for medical graduates and post graduate trainees with regards to specialisation decision preferences. Study design Mixed method Place and duration of study: Study conducted at sandmen provincial hospital from 1st September to 30th December 2021. Methodology: This was two phase sequential mixed method study. The first phase involved qualitative exploration through a semi-structured interview with post graduate trainees from various specialties who walked into the radiology department of Sandman Provincial Hospital Quetta with identification of theme and subtheme to develop a questionnaire. Questionnaire was designed to collect various opinions on the theme and sub-theme. Questionnaire included 11 items with two open ended questions and all other closed ended questions. Questionnaire was distributed to target population and demand survey was conducted by collecting questionnaire after a week. It was anonymous to ensure confidentiality and autonomy to participants. Results: The response rate was 71% while omitting the incomplete questionnaire. It was divided into two groups, 1) changed of speciality CS 8(16%), M-3(37%), F-5 (62%) and 2) without changed of speciality 43(84%), M-21(49%), F-22(51%).Results were also compiled by combining both the groups as total participants to check the variation in opinion. The availability of structured career counselling for specialty selection will lessen the burden of decision making, total participants agreed were 44(86%), not in favour were 6(12%) and one answered with don’t know (2%), NCS (36(84%); CS (8(100%). Conclusion: Based on results Medical Students are in demand of structured career counselling program to ease the decision of speciality preference and in favour of incorporating it in medical education to avoid stress and other difficulties faced by them. Keywords: Structured career counselling, change of speciality (CS), Post graduate trainee,